Implementation of workbooks as an active learning tool for Industrial Design Engineering - Wikberg Nilsson, Åsa; Törlind, Peter (Luleå tekniska universitet, Människa och teknik, 2020)
This paper focuses on the workbook approach. It is a tool for active and self-regulated learning, allowing for teachers to guide students in a certain direction and to provide clear goals in otherwise rather open-ended design projects. The learning strategies self-regulated students employ support setting up goals and evaluate their performance, this strategy is guided by the workbook approach. Hence, it supports also previously non-self-regulated learners in devoting to the projects in more informed ways. Industrial design engineering is unique compared to other engineering educations as it combines both artistic and scientific approaches and practices, it combines technical rationality and reflective practice. Typical design projects address the social, economical, cultural, material and technical dimensions of a situation in iterative design thinking cycles of gaining empathy for user needs, visualizing and materializing ideas and concepts and testing with users to inform the process. The workbook approach is a tool to guide such open-ended projects through cycles of reflection in- and on- actions. This informs learning and understanding during the process, rather than afterwards when final results is done. The workbook approach is currently implemented in five compulsory and several elective courses at Industrial Design Engineering (IDE) at Luleå University of Technology (LTU). The results so far are indications of better self-regulation in subsequent courses and students’ understandings of the end-result not being the project result, but for them to be the next generation of independent design engineers. As of yet, this is a work-in-progress and more studies are needed to provide evidence of concept such as more active and/or self-regulated learners. The workbook approach however seems to contribute in students being more independent as it guides them through the project process. In conclusion, based on our preliminary findings, we consider that the workbook approach shows indications of being a tool to ...